Spectroscopic and nuclear analytical studies of archaeological pottery samples recently excavated from Uraiyur, Tamilnadu, India - Tamilarasu, S.; Velraj, G.; Acharya, R.; Reddy, A. V. R.; Swain, K. K.; Basavaiah, N. (My University, 2015)
These studies focus on firing temperature, elemental study and provenance studies of the ancient pottery collected from the recently excavated site in Uraiyur in Tamilnadu, South India. The samples were subjected to analysis as in the received state. Fourier Infrared Spectroscopy (FTIR), Particle induced X-ray emission (PIXE) and The Particle induced gamma ray emission (PIGE). PIXE has been proved to be a very rapid and accurate method for the elemental analysis of ancient artifacts. Using protons whose energy is lower than 3 MeV, it is possible to obtain, in a few minutes, the actual composition of narrow parts of artifacts, without any sampling, even at microscopic level. (PIGE) method using 4 MeV proton beam was standardized for simultaneous determination of Si, Al and Na for archaeological pottery samples. The FTIR studies using to analysis the firing temperature and the firing conditions adopted at the time of manufacturing of the pottery also determined. The Uraiyur samples were fired in the range of 700-800 °C. The PIXE and PGE results provided persuasive evidence Uraiyur pottery used at least two different clay sources. The cause of the distinct group separation could be because of the possible exchange between communities, as it is known that communities, which produced these wares, did not live in isolation from each other.
Keywords: Provenance study; PIXE; PIGE; Uraiyur pottery; FTIR; Uraiyur